Effect of functional strength training on certain physical variables and kick of Twimeo Chagi among young taekwondo players - Elsawy, G. (World Journal of Sport Sciences, 2010)
The present study examined the Effect of functional strength training on strength, balance and performance level of Twimeo Chagi among Taekwondo Young Players. Twenty four young taekwondo players (mean +/- SD age, 13 +/- 1.9 years), divided into (2) group (experimental group -12 players) and (control group -12 players), the experimental group performed the functional strength training for (8) weeks. The tests was measured before and after the training program, the results indicated that, The increased significantly for balance and performance level of Twimeo Chagi after the training program and no increased significantly for Power, These data show that functional strength training can cause an increase, balance and performance level of Twimeo Chagi among Taekwondo Young Players.